2021
DOI: 10.1101/2021.05.04.21256648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study protocol: Strengthening understanding of effective adherence strategies for first-line and second-line antiretroviral therapy (ART) in selected rural and urban communities in South Africa

Abstract: Multiple factors make adherence to antiretroviral therapy (ART) a complex process. This study aims to describe the barriers and facilitators to adherence for patients receiving first-line and second-line ART, identify different adherence strategies utilized and make recommendations for an improved adherence strategy. This mixed method parallel convergent study will be conducted in seven high volume public health facilities in Gauteng and one in Limpopo province in South Africa. The study consists of four phas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…This systematic review has been designed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) [ 23 ] (Supplementary Material 1 ), following the registered protocol on the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42019127564) [ 24 ]. The study used Population (P), Interventions (I), Comparisons (C) and Outcomes (O) (PICO) criteria as the search strategy tool.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review has been designed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) [ 23 ] (Supplementary Material 1 ), following the registered protocol on the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42019127564) [ 24 ]. The study used Population (P), Interventions (I), Comparisons (C) and Outcomes (O) (PICO) criteria as the search strategy tool.…”
Section: Methodsmentioning
confidence: 99%